A dosimetric comparison of non-coplanar volumetric modulated arc therapy and non-coplanar fixed field intensity modulated radiation therapy in hippocampus-avoidance whole-brain radiation therapy with a simultaneous integrated boost for brain metastases - Zeng, Huaqu; Zhong, MinZhi; Chen, Zongyou; Tang, Shukui; Wen, Zunbei (Frontiers in Oncology, 2025)
ObjectiveThe aim of this study was to investigate the dosimetric differences between non-coplanar volumetric modulated arc therapy (VMAT) and non-coplanar fixed-field intensity-modulated radiotherapy (IMRT) in hippocampus-avoidance whole-brain radiation therapy with a simultaneous integrated boost (HA-WBRT+SIB) for brain metastases using the Monaco treatment planning system (TPS).MethodA total of 22 patients with brain metastases were retrospectively enrolled. Two radiotherapy treatment plans were designed for each patient: non-coplanar VMAT and non-coplanar fixed field IMRT. The dose distribution of targets and organs at risk (OAR), the number of monitor units (MUs), and pre-treatment plan verification were compared between the two plans while meeting the prescribed dose requirements of the target volume.ResultsThere were no significant differences in V50, V55, Dmax, heterogeneity index (HI) and conformity index (CI) of target PGTV between the two plans (p>0.05). For PTV-brain-SIB, there was no significant difference in D98% between IMRT and VMAT (p=0.103). VMAT significantly improved the V30 of PTV-brain-SIB (p<0.001), decreased HI (p=0.003), and increased CI (p<0.001). There were no significant differences in the Dmax to the brain stem, left and right lens, optic chiasm, pituitary gland, and left and right hippocampus between the two plans (p>0.05). Compared with IMRT, VMAT significantly reduced the Dmax to the left and right eyes (p<0.001) and significantly increased the Dmax to the right inner ear (p=0.010). There was no significant difference in the Dmax to the left inner ear between VMAT and IMRT (p=0.458). Compared with IMRT, VMAT significantly reduced the Dmax to the left optic nerve (p=0.006), but significantly increased the Dmax to the right optic nerve (p=0.001). There was no significant difference in the Dmax to the left and right hippocampus between VMAT and IMRT (p>0.05), but VMAT significantly increased the D100% (p<0.05) compared with IMRT. Compared with VMAT, IMRT significantly reduced the MU (p<0.001) but VMAT has a higher treatment efficiency than IMRT, with an average reduction of 41 seconds (294.1 ± 16.4 s for VMAT, 335.8 ± 34.9 s for IMRT, p<0.001). Under the conditions of 3%/2 mm, and 2%/2 mm, the gamma passing rate of the IMRT QA was improved compared to VMAT, with an average increase of 0.6%, p=0.013, and 1.7%, p<0.001, respectively.ConclusionBoth non-coplanar VMAT and non-coplanar fixed field IMRT based on the Monaco TPS produce clinically acceptable results for HA-WBRT+SIB in patients with brain metastases. Compared with IMRT, VMAT has better dose distribution in the target volume and treatment efficiency, but IMRT can better protect the hippocampus and reduce the number of MUs.